Correction to: Association of PM2.5 concentration with health center outpatient visits for respiratory diseases of children under 5 years old in Lima, Peru - Jennifer Estefanía Davila Cordova; Vilma Tapia Aguirre; Vanessa Vasquez Apestegui; Luis Ordoñez Ibarguen; Bryan N. Vu; Kyle Steenland; Gustavo F. Gonzales (BMC, 2020)
The original version of this article [1], published on 15 January 2020, contained incorrect name of the co- author. In this Correction the affected part of the article is shown.